Moral Suasion: An alternative tax policy strategy? Evidence from a controlled field experiment in Switzerland - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2004)
In a controlled field experiment in Switzerland this paper analyses the effects of moral suasion on the timely paying and filling out of the tax form 2001, and the honesty regarding the declaration of domestic income from capital gains, lottery winnings, and certain insurance benefits. Comparisons of different tax filling years and multiple regression estimations have been done using these three factors as dependent variables to check if there is a significant difference between the control group and the treatment group, controlling for additional factors that might influence compliance behaviour. In February 2002 the treatment group received a letter signed by the commune's fiscal commissioner containing normative appeals. Results indicate that moral suasion has hardly any effect on taxpayers' compliance behaviour. The strongest effect can be observed for the variable tax payments.
Keywords: H26; H71; 330; tax compliance; morale suasion; field experiment